The Mathematical Model of Relationship Between Population of Pod Sucking Bug Nezara viridula L. and Soybean Pod Damage : Model Matematika Hubungan Populasi Serangga Penghisap Polong Nezara viridula L. Dengan Kerusakan Polong Kedelai - Susilo, Achmadi (Journal of Applied Plant Technology, 2023)
The aims of this research are: (1) to predict the damage of soybean pod through the mathematical model of relationship between population density of N. viridula and pod damage, (2) to predict the soybean yield through the mathematical model of relationship between population density of N. viridula and pod damage where made by modification of Reynolds Transport Theorem. This research was used Completely Randomized Design with nine treatments and each was replicated three times. The treatment were : P0 = control, P1 = 1 nymph, P2 = 2 nymphs, P3 = 3 nymphs, P4 = 4 nymphs, P5 = 1 adult, P6 = 2 adults, P7 = 3 adults, and P8 = 4 adults. The population density of pod sucking bug was the independent variable, while dependent variables were : rate of pod damage, and dry pod weigh. Analysis of mathematical modeling was made by approaching of Continuum Theory and Reynolds Transport Theorem. The results showed that : (1) Relationship between population of N. viridula and pod damages in the form of mathematical model which is used to predict the soybean pod damage has error 0,02 – 0,10%, and (2) Mathematical model where made by modification of Reynolds Transport Theorem which is used to predict the soybean yield has error 0,01 – 1,00%.